Smooth Muscle Cell—Macrophage Interactions Leading to Foam Cell Formation in Atherosclerosis: Location, Location, Location - Xiang, Pinhao; Blanchard, Valentin; Francis, Gordon A. (Frontiers in Physiology, 2022)
Cholesterol-overloaded cells or “foam cells” in the artery wall are the biochemical hallmark of atherosclerosis, and are responsible for much of the growth, inflammation and susceptibility to rupture of atherosclerotic lesions. While it has previously been thought that macrophages are the main contributor to the foam cell population, recent evidence indicates arterial smooth muscle cells (SMCs) are the source of the majority of foam cells in both human and murine atherosclerosis. This review outlines the timeline, site of appearance and proximity of SMCs and macrophages with lipids in human and mouse atherosclerosis, and likely interactions between SMCs and macrophages that promote foam cell formation and removal by both cell types. An understanding of these SMC-macrophage interactions in foam cell formation and regression is expected to provide new therapeutic targets to reduce the burden of atherosclerosis for the prevention of coronary heart disease, stroke and peripheral vascular disease.